Efficient and Opportunistic Choices of Accounting Procedures: Corporate Control Contests - Christie, Andrew A.; Zimmerman, Jerold L. (The Accounting Review, 1994)
[Accounting numbers are an integral part of the firm's formal and informal contracts (Watts 1974; Holthausen and Leftwich 1983; Watts and Zimmerman 1986; Ball 1989; Christie 1990). This contracting-based theory of accounting is based on the premise that managers choose particular accounting procedures either efficiently to maximize the value of the firm, or opportunistically to make the manager better off at the expense of some other contracting party (Holthausen 1990). The relative amounts of efficiency and opportunism depend on controls on managers' accounting discretion. Such controls include monitoring by the board of directors, competition from the product markets and from within the firm by other managers, and the discipline of the market for corporate control. It is difficult to determine whether managers make accounting choices to maximize firm-value. Empirical tests often assume opportunism and usually reject the null hypothesis of no association between accounting choice and firm-specific variables such as leverage (Christie 1990). However, many of the empirical regularities interpreted as evidence of opportunism can also be interpreted as occurring for efficiency reasons, which serves to confound these findings (Watts and Zimmerman 1986; Watts and Zimmerman 1990; Sweeney 1994). The few tests based on efficiency rationales find an association between the contracting variables and accounting choice (Zimmer 1986; Whittred 1987; Malmquist 1990; Mian and Smith 1990a). This paper measures the relative influences of efficiency and opportunism in accounting choice by examining a non-random sample that maximizes the probability of finding opportunism. Economics and finance studies document that corporate control actions such as tender offers and proxy fights discipline opportunistic managers. Therefore, we select a sample of takeover targets and examine this sample for evidence of managerial opportunism in choice of accounting procedures. A key assumption of our tests is that, prior to the control action, corporate control targets contain more non-value-maximizing managers than surviving firms in the same industry that were not targets of corporate control actions. This assumption allows us to use surviving firms' accounting procedures as the benchmark for the efficient accounting choice. In this application of Alchian's (1950) "economic Darwinism," surviving firms on average are more efficient than non-surviving firms. An unbiased estimate of accounting opportunism in this sample is an estimate of the upper bound on the amount of accounting opportunism in a random sample of firms. If there is little or no opportunism in our non-random sample, then for firms generally we can discount opportunism as an explanation for choice of the three accounting methods we study. Efforts to explain choice of accounting methods could then be redirected towards efficiency explanations. We measure opportunism by comparing the frequency of choice of income-increasing procedures by takeover targets with the corresponding frequency of their surviving industry peers. We find that takeover targets select income-increasing depreciation, inventory, and investment tax credit (ITC) accounting methods more frequently than their surviving industry peers in up to 11 years preceding the control action. Our analysis includes a multiple regression that controls for efficient choice of accounting methods. Our estimate of the upper bound on the frequency of opportunism is small relative to the mean choices of surviving firms. We conclude that some accounting opportunism exists in the takeover targets, but that efficiency is the more important explanation of accounting choice. However, while the frequency of opportunism is relatively small, the dollar effect on retained earnings of selecting an income-increasing method is large. For the median target firm, the after-tax effect on retained earnings if the firm had been on the alternative method is about 26 percent for depreciation, 9 percent for inventory, and around 5 percent for the ITC.]